Challenges and opportunities in the transition from product to service innovation Idea management as a vital first step in the servitisation journey for the manufacturing industry - Bååt, Malin; Jabraouti, Safwan (My University, 2023)
In today's manufacturing industry, firms adapt to survive and grow by transitioning from solely producing physical products to providing services. However, this shift presents a significant challenge that requires a robust innovation process to generate and invest in promising ideas that benefit both customers and the company. This research examines how idea management can serve as the initial stage of the innovation process and facilitate the transition towards servitisation. The authors seek to investigate the effectiveness of idea management in supporting this shift, and how the involvement of employees and customers can influence the service innovation process for manufacturing companies. The empirical findings stressed that increasing the number of ideas at the beginning of the idea management stage through engaging customers and employees and then moving through a systematic selection process are important prerequisites for service innovation. The idea management process needs to be collaborative with customers and frontline employees and have functions in place to manage knowledge exchange and ideas. Alignment between service and product development was found to be an essential success factor for service innovation. Finally, the research identified a need for manufacturing firms to establish a closer relationship with end users and not only focus on involving distributors. Managerial implications for managers of manufacturing firms highlight support and encouragement for employees on all levels to participate in innovation and achieve a companywide initiative towards servitisation.
Keywords: servitisation; idea management; service innovation; manufacturing; digitalisation